Exploration on traffic characteristics and gap assessment on midblock U-turn facilities - Mohamad Hilmi, Hamizan (2018)
The idea of a Midblock U-turn Opening installation is to eliminate direct right turns. Midblock U-turning facilities are median openings on multi-lane highways. Uturning facilities aimed at easing traffic conflicts and pressures at highway intersections. This study is to identify the influence of midblock U-turn facilities towards traffic parameters of speed, flow and density relationship and to determine the safe merging gap for the midblock U-turn facilities. This study is referring to unsignalized junction, that is the midblock U-turn facilities located at Jalan Tanah Putih, heading to Kuantan, Pahang. The traffic characteristics of this study is to define the speed, flow and density when the vehicle at free flow speed and when reaching the conflict point near the midblock U-turn facilities. Raff’s Method is the method used to analysed the critical gap for the passenger car that want to make a U-turn. By using Raff Method, the gap acceptance and gap rejected will be observe and from these data, it can produce a linear graph which can determined the critical gap. The result obtained showed the traffic characteristics relationship which is speed, flow and density that the data relationship was similar to Greenshield Model and critical gap of the U-turn was 5.0 second. The critical gap was comply with the standard of Malaysia Public Work Department and Transportation Research Board. The result show from the speed, flow and density relationship, the road was in a good condition and the drivers behavior that desire to merge into major road from the U-turn.